Nonenzymatic glucose detection in human serum using Ni nanoparticles decorated reduced graphene oxide - Waichal, Rupali; Bhirud, Ashwini; Fouad, H.; Gosavi, Suresh; Ashokkumar, Muthupandian (Science of Advanced Materials, 2020)
Reduced Graphene oxide (RGO) decorated with Ni nanoparticles (NiNPs) composites, have been successfully synthesized using a simple hydrothermal method and possessing excellent electrocatalytic activity towards glucose oxidation. The morphological and structural features of RGO-Ni nanocomposites were characterized by field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS) and energy dispersive spectroscopy (EDS). From TEM, we observed that NiNPs were anchored on RGO sheets. Cyclic Voltammetric (CV) study revealed that the electrocatalytic activity of RGO-Ni nanocomposite with 20% Ni loading (RGONi-20) towards glucose oxidation is better than that shown by bare Glassy Carbon Electrode (GCE), RGO, bare NiNPs, RGONi10 and RGONi-30. The prepared nanocomposites exhibited fast electrocatalytic response (<5 s) towards glucose oxidation. Amperometric study indicates that the present glucose sensor have exhibited excellent performance by offering a lowest detection limit as 5.1 mu M, with linier range from 2 to 5000 mu M and high sensitivity of 896.67 mu A mM(-1) cm(-2). Interference from different anticipatable electroactive substances such as ascorbic acid (AA), uric acid (UA) and dopamine (DA) is not observed. Furthermore, the application of the as prepared sensor was successfully demonstrated for the detection of glucose in human serum and results were comparable to presently used nonenzymatic technique. RGONi-20 nanocomposite electrode holds great promise for the development of biosensors and other electrochemical devices.
Keywords: Electrochemical; Glucose Sensor; Graphene-Nickel Nanoparticles; hydrothermal; Nanocomposite; Nonenzymatic